UPAYA ADAPTASI PENDUDUK BERTAHAN TINGGAL DI KAWASAN RAWAN BANJIR DESA BENA KECAMATAN AMANUBAN SELATAN KABUPATEN TIMOR TENGAH SELATAN. - Ton, Welmi; Samin, Mikael; Sunimbar, Sunimbar (Jurnal Geografi, 2024)
South Central Timor Regency is one of the districts in East Nusa Tenggara Province which often experiences flooding during the rainy season, as happened in South Amanuban District, especially in Bena Village. This research aims to: (1) To find out the forms of adaptation efforts of the population to survive living in the area prone to flooding, Bena village, South Amanuban District, South Central Timor Regency; (2) To analyze the level of vulnerability to flood disasters in Bena Village, South Amanuban District, South Central Timor Regency. This type of research is descriptive qualitative. The descriptive type aims to answer questions about who, what, when, where and how it is related to certain research. Descriptive research is used to obtain information about the variables or conditions of a situation. The informants in this research were actually flood victims in Bena Village, South Amanuban District, South Central Timor Regency. Data Source Consists of primary data and secondary data. Data collection techniques are: observation, interviews, and documentation. The data analysis techniques used are: data collection, data reduction, data presentation, and drawing conclusions. Research Results: (1) Based on the research results, it shows that the adaptation efforts of the population to survive living in areas prone to flood disasters in Bena Village are divided into 2 forms of adaptation efforts, namely active adaptation efforts and passive adaptation efforts; (2) Based on six parameters, namely soil type, elevation/place height, slope slope, land use, rainfall, and river density, the Bena Village area has three zones of flood vulnerability level, namely the non-prone zone, the moderately vulnerable zone and the moderate/prone zone flood.